Patients’ Perspective of Comprehensive Parkinson Care in Rural Victoria - Robert Iansek; Mary Danoudis (Parkinson's Disease)
Introduction. There is a higher prevalence of Parkinson’s disease (PD) in rural Australia and a poorer perceived quality of life of rural Australians with PD. Coordinated multidisciplinary teams specialised and experienced in the treatment of PD are recommended as the preferred model of care best able to manage the complexities of this disorder. There remains a lack of team-based specialised PD services in rural Australia available to people living with PD. This study aims to explore how the lack of specialised PD services impacts on the person’s experiences of the health care they receive in rural Victoria. This study compared the health-care experiences of two different cohorts of people with PD living in rural Victoria; one cohort living in East Gippsland have had an established comprehensive care model implemented with local trained teams and supported by a metropolitan PD centre, and the other cohort was recruited from the remainder of Victoria who had received standard rural care. Methods. This descriptive study used a survey to explore health-care experiences. Questionnaires were mailed to participants living in rural Victoria. Eligibility criteria included having a diagnosis of PD or Parkinsonism and sufficient English to respond to the survey. The validated Patient-Centred Questionnaire for PD was used to measure health-care experiences. The questions are grouped accordingly under one of the 6 subscales or domains. Outcomes from the questionnaire included summary experience scores (SES) for 6 subscales; overall patient-centeredness score (OPS); and quality improvement scores (QIS). Secondary outcomes included health-related quality of life using the disease-specific questionnaire PDQ39; disease severity using the Hoehn and Yahr staging tool; and disability using the Movement Disorders Society-Unified Parkinson’s Disease Rating Scale, part II. Results. Thirty-nine surveys were returned from the East Gippsland group and 68 from the rural group. The East Gippsland group rated significantly more positive the subscales “empathy and PD expertise,” P=0.02, and “continuity and collaboration of professionals,” P=0.01. The groups did not differ significantly for the remaining 4 subscales (P>0.05) nor for the OPS (P=0.17). The QIS showed both groups prioritised the health-care aspect “provision of tailored information” for improvement. Quality of life was greater (P<0.05) and impairment (P=0.012) and disability were less (P=0.002) in the East Gippsland group. Conclusion. Participants who received health care from the East Gippsland program had better key health-care experiences along with better QOL and less impairment and disability. Participants prioritised provision of information as needing further improvement.